Primary rhegmatogenous retinal detachment: 20 years of change - Minihan, M. (2001)
AIM—To compare characteristics, management, and outcome of two groups of patients with primary rhegmatogenous retinal detachment (RRD) presenting to the same vitreoretinal unit approximately 20 years apart. METHODS—124 patients in 1979-80 and 126 cases in 1999 were compared. RESULTS—More cases were pseudophakic and fewer aphakic in 1999 than 1979-80. More cases of giant retinal tear and fewer dialyses were operated on in 1999. Vitrectomy was a primary procedure in 63% of cases in 1999 but only 1% in 1979-80. Anatomical success rates were statistically similar: 79.8% primary and 88.8% final success in 1979-80, and 84% primary and 93.6% final success in 1999. CONCLUSION—Surgical management of primary RRD has changed greatly in 20 years. Success rates have changed little, despite availability of differing surgical techniques.